Traumatic renal artery thrombosis: a case report and literature review - Xia, Xiaohua; Zhao, Guang; Feng, Qiupeng; Guo, Zhiqiang; Ma, Jin; Yuan, Hua (Frontiers in Medicine, 2024)
Traumatic Renal Artery Thrombosis (TRAT) is an uncommon condition characterized by a low clinical incidence and a lack of specific symptoms, making it highly susceptible to being overlooked or misdiagnosed. This retrospective analysis aims to review the diagnostic and therapeutic approaches applied to a TRAT patient who received successful treatment in the Emergency Medicine Department of the First People’s Hospital of Kunshan. The objective is to enhance clinicians’ comprehension of TRAT, promote early diagnosis and intervention, and ultimately improve patient outcomes.